2018
DOI: 10.3390/jcs2020029
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Electrode Configurations for Two-Probe, Four-Probe and Multi-Probe Schemes in Electrical Resistance Tomography for Delamination Identification in Carbon Fiber Reinforced Composites

Abstract: Internal damage in Carbon Fiber Reinforced Polymer (CFRP) composites modifies the internal electrical conductivity of the composite material. Electrical Resistance Tomography (ERT) is a non-destructive evaluation (NDE) technique that determines the extent of damage based on electrical conductivity changes. Implementation of ERT for damage identification in CFRP composites requires the optimal selection of the sensing sites for accurate results. This selection depends on the measuring scheme used. The present w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…13 Electrode location and the layup influence the electric current path inside the material 11,14 making some interlaminar regions inaccessible 12,15 affecting accuracy in damage size and location quantification. 10,13,16,17 Accurate and sensitive damage identification using electrical resistance or potential changes is possible if the sensing locations cover large surface regions. Nevertheless, a large number of sensors and the factorial increase of sensing combinations significantly increases hardware and computational costs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 Electrode location and the layup influence the electric current path inside the material 11,14 making some interlaminar regions inaccessible 12,15 affecting accuracy in damage size and location quantification. 10,13,16,17 Accurate and sensitive damage identification using electrical resistance or potential changes is possible if the sensing locations cover large surface regions. Nevertheless, a large number of sensors and the factorial increase of sensing combinations significantly increases hardware and computational costs.…”
Section: Introductionmentioning
confidence: 99%
“…Other works have studied optimization for ERT damage identification in CFRP composites. 10,17 These works have used a sensor optimization measure known as effective independence (EI). 52,53 The EI-based optimization has been applied to reduce the number of electrical resistance measurements from two-probe schemes, 10 and it has been extended to electric potential measurements using four-probe and multi-probe schemes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few groups have used the EIT approach addressing electrode configurations located either at the in-plane surfaces or through the thickness of the laminate. In this regard, Escalona-Galvis et al (2018) used finite element analysis to study the optimal electrode configuration to detect delamination in carbon fiber reinforced composites; they found that damage identification is influenced by the electrodes configuration, and their simulations report better results for in-plane measurements than for through-thickness ones. However, Zhang et al (2012) used EIT with through-thickness and in-plane electrode configurations to correlate the electrical signal with visible damage caused by several impacts on carbon black/glass fiber composites.…”
Section: Introductionmentioning
confidence: 99%